A biodegradable medical bandage and a method of making the same
Patent Information
- Application Number
- CN202610996753.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-06
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-07-06
AI Technical Summary
但是该专利技术需要加入二氧化钛且抑菌亲肤聚乳酸的制备过程较为复杂,抑菌效果也需要进一步提升,同时也缺乏对绷带顶破强力的研究
(1)本发明以丙烯酸酯接枝聚乳酸作为油相、以改性明胶作为水相、以司班80为乳化剂,通过混合乳化得到纺丝乳液,配合改性壳聚糖微球共同进行电吹纺丝,最后进行光照交联得到生物降解的医用绷带;通过可降解材料丙烯酸酯接枝聚乳酸和改性壳聚糖微球的共同作用,既保证良好的抑菌效果,又能够提升材料的顶破强力。
Smart Images

Figure CN122479176B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of medical bandage material technology, specifically relating to a biodegradable medical bandage and its preparation method. Background Technology
[0002] As a medical textile, bandages prevent secondary damage to wounds, regulate the temperature and humidity of wound tissue, effectively reduce complications and wound infection, and greatly improve patient comfort. Medical bandages, as common medical textiles, are indispensable materials in surgical procedures. Early pure cotton bandages caused secondary damage to wounds due to their fuzzy texture, while elastic bandages, by overemphasizing elasticity, neglected the body's physiological needs such as blood circulation. With technological advancements, the manufacturing process of medical bandages has become quite mature, encompassing various forming methods such as knitting, weaving, and non-woven fabrication. An ideal medical bandage must possess both softness and elasticity, as well as excellent physical and mechanical properties and wound protection capabilities.
[0003] Biodegradable medical bandages are polymeric materials that can be decomposed into non-toxic small molecules by microorganisms or chemical reactions in a specific environment or in the human body. Unlike traditional plastic or cotton bandages, they not only provide physical support and fixation, but also promote wound healing or avoid secondary trauma through their own degradation process, which is a green trend in the medical field. Biodegradable medical bandages have the following characteristics: (1) Avoiding secondary surgical trauma: Biodegradable bandages can soften and dissolve under certain conditions, or be gradually absorbed in the body, thus avoiding the pain caused by forced removal. (2) Promoting wound healing: Some biodegradable materials have extremely high hydrophilicity, which can achieve hemostasis by providing a moist healing environment, and can also provide a scaffold for cell growth and accelerate tissue repair. (3) Environmentally friendly: They will not cause white pollution after disposal and meet green medical standards.
[0004] Chinese patent (publication number CN117618624B) discloses a biodegradable medical polymer bandage and its preparation method. This medical polymer bandage first prepares an antibacterial and skin-friendly polylactic acid (PLA). The antibacterial and skin-friendly PLA is obtained by reacting carboxyl-modified chitosan, epoxy-based quaternary ammonium salt, and hydrophilic-modified PLA. The carboxyl-modified chitosan and epoxy-based quaternary ammonium salt modify the hydrophilic-modified PLA, linking the three components through chemical bonds, increasing its cross-linking degree, improving its mechanical properties, increasing the number of active groups, enhancing its cell adhesion ability, and improving its antibacterial and antiviral properties. It also exhibits excellent biodegradability. However, this patented technology requires the addition of titanium dioxide, and the preparation process of the antibacterial and skin-friendly PLA is relatively complex. The antibacterial effect also needs further improvement, and research on the bandage's puncture resistance is lacking.
[0005] Therefore, there is an urgent need for a biodegradable medical bandage that, without the addition of titanium dioxide, can ensure good antibacterial properties and significantly improve the material's burst strength through component design and the introduction of functional materials. Summary of the Invention
[0006] To address the shortcomings of existing technologies, the present invention aims to provide a biodegradable medical bandage and its preparation method. The invention first mixes polylactic acid raw materials and maleic anhydride and then melt-blends them to obtain product A. Next, glycidyl methacrylate is used to graft product A to obtain acrylate-grafted polylactic acid. The acrylate-grafted polylactic acid is then added to an organic solvent and stirred to dissolve, obtaining an oil phase. Methacrylate-modified gelatin and photoinitiator LAP are added to water and stirred to dissolve, obtaining an aqueous phase. The oil phase, aqueous phase, and Span 80 are mixed and emulsified to obtain a spinning emulsion. Finally, modified chitosan microspheres and the spinning emulsion are spray-coated, electrospun, and photocrosslinked to obtain a biodegradable medical bandage.
[0007] The technical solution adopted by the present invention to solve the above-mentioned technical problems is as follows: In a first aspect, the present invention provides a method for preparing a biodegradable medical bandage, comprising the following steps: S1. First, polylactic acid raw material and maleic anhydride are mixed and melt-blended to obtain product A. Then, glycidyl methacrylate is used to graft product A to obtain acrylate-grafted polylactic acid. S2. The acrylate-grafted polylactic acid is added to an organic solvent and stirred to dissolve to obtain an oil phase. The methacrylate-modified gelatin and photoinitiator LAP are added to water and stirred to dissolve to obtain an aqueous phase. The oil phase, aqueous phase and Span 80 are mixed and emulsified to obtain a spinning emulsion. S3. The modified chitosan microspheres and the spinning emulsion are sprayed, electrospun, and photocrosslinked to obtain a biodegradable medical bandage.
[0008] As a preferred technical solution of the present invention, the preparation steps of the spinning emulsion in step S2 are as follows: by weight, 8-10 parts of acrylate-grafted polylactic acid are added to 90-100 parts of organic solvent and stirred to dissolve to obtain an oil phase; 2-4 parts of methacrylate-modified gelatin and 0.2-0.4 parts of photoinitiator LAP are added to 20-30 parts of deionized water and stirred to dissolve at 40-50°C to obtain an aqueous phase; 90-100 parts of the oil phase, 20-30 parts of the aqueous phase and 1-2 parts of Span 80 are mixed and homogenized and emulsified at a speed of 5000-6000 r / min for 8-10 min to obtain a spinning emulsion.
[0009] As a preferred technical solution of the present invention, the organic solvent in step S2 is dichloromethane or trichloromethane.
[0010] As a preferred technical solution of the present invention, the conditions for spraying-electroblotting in step S3 are as follows: the voltage of the electroblotting of the spinning emulsion is 12~16kV, the airflow velocity is 40~50m / s; and the spraying flow rate of the modified chitosan microspheres is 0.1~0.2mL / min.
[0011] As a preferred technical solution of the present invention, the preparation step of product A in step S1 is as follows: 90-100 parts by weight of polylactic acid raw material, 1.8-2.4 parts by weight of maleic anhydride and 0.2-0.4 parts by weight of triethylamine are mixed and added to a torque rheometer, and melt-blended at 30-40 r / min for 50-60 min at 160-170°C to obtain product A.
[0012] As a preferred technical solution of the present invention, the grafting treatment step S1 is as follows: by weight, 90-100 parts of product A are added to 280-300 parts of xylene at 40-50°C and stirred at 340-360 r / min to dissolve. After heating to 70-80°C, 2.4-2.8 parts of glycidyl methacrylate and 0.6-0.8 parts of triethylamine are added for grafting treatment for 40-50 min. After the reaction is completed, 180-200 parts of acetone are added to precipitate the precipitate. The precipitate is filtered and vacuum dried to obtain acrylate-grafted polylactic acid.
[0013] This invention involves mixing polylactic acid raw material, maleic anhydride, and triethylamine catalyst and then adding the mixture to a torque rheometer. Maleic anhydride is grafted onto the polylactic acid molecular chain through melt blending. Glycidyl methacrylate is then used for grafting treatment. The epoxy groups of glycidyl methacrylate react with the anhydride to prepare acrylate-grafted polylactic acid containing unsaturated double bonds.
[0014] As a preferred technical solution of the present invention, the method for preparing the modified chitosan microspheres is as follows: maleic anhydride is used to modify chitosan powder to obtain modified chitosan; the modified chitosan, liquid paraffin and emulsifier are mixed and then emulsified and crosslinked to obtain modified chitosan microspheres.
[0015] In this invention, maleic anhydride undergoes an amidation reaction with the amino groups on the chitosan molecular chain, introducing carboxyl groups and carbon-carbon double bonds into the chitosan backbone, effectively achieving the preparation of modified chitosan. Subsequently, the modified chitosan is dissolved in acetic acid solution to form an aqueous phase, with liquid paraffin as the oil phase. An emulsion is prepared by adding an emulsifier, and then glutaraldehyde is added dropwise as a crosslinking agent to obtain modified chitosan microspheres with a three-dimensional network structure.
[0016] As a preferred technical solution of the present invention, the modification treatment steps are as follows: by weight, 10-12 parts of maleic anhydride are added to 400-500 parts of dimethyl sulfoxide and stirred to dissolve, then 8-10 parts of chitosan powder are added and dispersed evenly, and the modification treatment is carried out at 60-70°C for 6-8 hours, followed by washing with acetone and vacuum drying to obtain modified chitosan.
[0017] As a preferred technical solution of the present invention, the emulsification and crosslinking step is as follows: by weight, 2-4 parts of modified chitosan are added to 200-300 parts of acetic acid solution with a mass concentration of 1% and stirred to dissolve. Then, 800-900 parts of liquid paraffin and 20-30 parts of emulsifier are added. The mixture is first stirred and emulsified at 900-1000 r / min under the condition of 40-50°C for 30-40 min. Then, 90-100 parts of glutaraldehyde solution with a mass concentration of 10% are added dropwise to adjust the pH to 8-9 and crosslinking treatment is carried out for 2-4 h. The precipitate is collected by centrifugation, washed successively with petroleum ether and isopropanol, and vacuum dried to obtain modified chitosan microspheres.
[0018] As a preferred embodiment of the present invention, the emulsifier is selected from one or more of Span 20, Span 60 or Span 80.
[0019] The modified chitosan microspheres of this invention have good specific surface area and structural stability. When uniformly dispersed in the bandage matrix, they can serve as physical support points, effectively resisting external force damage and thus significantly improving the puncture strength of the bandage. In addition, the microsphere morphology of chitosan greatly increases the contact specific surface area between the material and bacteria, allowing the microspheres to more fully exert their electrostatic adsorption and membrane-breaking effects, ultimately achieving a good antibacterial effect.
[0020] A second aspect of the present invention provides a biodegradable medical bandage prepared by the preparation method described in the first aspect.
[0021] Compared with the prior art, the present invention has the following beneficial effects: (1) In this invention, acrylate-grafted polylactic acid is used as the oil phase, modified gelatin is used as the water phase, and Span 80 is used as the emulsifier. The spinning emulsion is obtained by mixing and emulsifying, and then electroblotting is carried out together with modified chitosan microspheres. Finally, photocrosslinking is carried out to obtain a biodegradable medical bandage. Through the combined action of the biodegradable materials acrylate-grafted polylactic acid and modified chitosan microspheres, both good antibacterial effect is ensured and the bursting strength of the material is improved.
[0022] (2) Under the action of photoinitiator LAP, the unsaturated acrylate double bonds of acrylate-grafted polylactic acid, methacrylate-modified gelatin and modified chitosan microspheres of the medical bandage of the present invention undergo free radical copolymerization and cross-linking to form a stable covalent cross-linking network, which effectively improves the structural density and overall stability of the bandage fabric, thereby improving the bursting strength; at the same time, the dense cross-linking structure can physically block the penetration and attachment of bacteria and microorganisms, combined with the chemical antibacterial mechanism of chitosan to destroy bacterial cell membranes and inhibit microbial proliferation, effectively improving the antibacterial rate of the material. Attached Figure Description
[0023] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0024] Figure 1 This is a schematic diagram of the cross-linking network formation mechanism in Embodiment 1 of the present invention. Detailed Implementation
[0025] To facilitate understanding of the present invention, the following embodiments are provided. Those skilled in the art should understand that these embodiments are merely illustrative and should not be construed as limiting the scope of the invention.
[0026] The sources of some components in the examples and comparative examples are as follows: Polylactic acid raw material, model L622E, was purchased from Guangdong Zhongsu Degradable Materials Co., Ltd. Maleic anhydride, CAS No. 108-31-6, was purchased from Sinopharm Chemical Reagent Co., Ltd. Triethylamine, CAS No. 121-44-8, was purchased from Sinopharm Chemical Reagent Co., Ltd. Glycidyl methacrylate, CAS No. 106-91-2, purchased from Sinopharm Chemical Reagent Co., Ltd. Ordinary gelatin, product number G108394, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. Methacrylate-modified gelatin, catalog number GM071350, with a degree of substitution of 50% and a molecular weight of 160kDa, was purchased from Zhejiang Muke Biotechnology Co., Ltd. Photoinitiator LAP, catalog number L1499100, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. Chitosan powder, product number C434547, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. Liquid paraffin, CAS No. 8042-47-5, purchased from Shanghai Maclean Biochemical Technology Co., Ltd. Span 20, CAS No. 1338-39-2, purchased from Sinopharm Chemical Reagent Co., Ltd. Span 60, CAS No. 1338-41-6, purchased from Sinopharm Chemical Reagent Co., Ltd. Span 80, CAS No. 1338-43-8, purchased from Sinopharm Chemical Reagent Co., Ltd. Example 1
[0027] This embodiment provides a method for preparing a biodegradable medical bandage, including the following steps: S1. By weight, 100 parts of polylactic acid raw material, 2.4 parts of maleic anhydride and 0.4 parts of triethylamine were mixed and added to a torque rheometer. The mixture was melt-blended at 170°C and 40 r / min for 50 min to obtain product A. At 50°C, 100 parts of product A were added to 300 parts of xylene and stirred at 360 r / min to dissolve. After heating to 80°C, 2.8 parts of glycidyl methacrylate and 0.8 parts of triethylamine were added for grafting treatment for 40 min. After the reaction was completed, 200 parts of acetone were added to precipitate the product. The precipitate was filtered and dried under vacuum to obtain acrylate-grafted polylactic acid.
[0028] S2. By weight, 10 parts of acrylate-grafted polylactic acid are added to 100 parts of organic solvent dichloromethane and stirred to dissolve to obtain an oil phase. 4 parts of methacrylate-modified gelatin and 0.4 parts of photoinitiator LAP are added to 30 parts of deionized water and stirred to dissolve at 50°C to obtain an aqueous phase. 100 parts of the oil phase, 30 parts of the aqueous phase, and 2 parts of Span 80 are mixed and homogenized at 6000 r / min for 8 min to obtain a spinning emulsion.
[0029] S3. The modified chitosan microspheres and the spinning emulsion are subjected to spray-coating-electroblotting. The voltage for electroblotting the spinning emulsion is 16kV, and the airflow velocity is 50m / s. The spraying flow rate of the modified chitosan microspheres is 0.2mL / min. Photocrosslinking is performed (wavelength 365nm, light intensity 25mW / cm², time 20s) to obtain a biodegradable medical bandage. The crosslinking network formation mechanism is as follows: Figure 1 As shown.
[0030] Preparation of the modified chitosan microspheres: By weight, 12 parts of maleic anhydride were added to 500 parts of dimethyl sulfoxide and stirred to dissolve. Then, 10 parts of chitosan powder were added and dispersed evenly. The mixture was modified at 70°C for 6 hours, washed with acetone, and vacuum dried to obtain modified chitosan. 4 parts of modified chitosan were added to 300 parts of 1% acetic acid solution and stirred to dissolve. Then, 900 parts of liquid paraffin and 30 parts of emulsifier Span 20 were added. The mixture was first emulsified at 50°C and 1000 r / min for 30 minutes. Then, 100 parts of 10% glutaraldehyde solution were added dropwise to adjust the pH to 9 and crosslinking was performed for 2 hours. The precipitate was collected by centrifugation, washed successively with petroleum ether and isopropanol, and vacuum dried to obtain modified chitosan microspheres. Example 2
[0031] This embodiment provides a method for preparing a biodegradable medical bandage, including the following steps: S1. By weight, 90 parts of polylactic acid raw material, 1.8 parts of maleic anhydride and 0.2 parts of triethylamine were mixed and added to a torque rheometer. The mixture was melt-blended at 30 r / min for 60 min at 160 °C to obtain product A. At 40 °C, 90 parts of product A were added to 280 parts of xylene and stirred at 340 r / min to dissolve. After heating to 70 °C, 2.8 parts of glycidyl methacrylate and 0.6 parts of triethylamine were added for grafting treatment for 40 min. After the reaction was completed, 180 parts of acetone were added to precipitate the precipitate. The precipitate was filtered and dried under vacuum to obtain acrylate-grafted polylactic acid.
[0032] S2. By weight, 8 parts of acrylate-grafted polylactic acid are added to 90 parts of organic solvent chloroform and stirred to dissolve to obtain an oil phase. 2 parts of methacrylate-modified gelatin and 0.2 parts of photoinitiator LAP are added to 20 parts of deionized water and stirred to dissolve at 40°C to obtain an aqueous phase. 90 parts of the oil phase, 20 parts of the aqueous phase, and 1 part of Span 80 are mixed and homogenized and emulsified at 6000 r / min for 8 min to obtain a spinning emulsion.
[0033] S3. The modified chitosan microspheres and the spinning emulsion are sprayed and electrospun. The voltage of the electrospinning emulsion is 12kV and the airflow velocity is 40m / s. The spraying flow rate of the modified chitosan microspheres is 0.1mL / min. Photocrosslinking is performed (wavelength is 365nm, light intensity is 15mW / cm², time is 30s) to obtain a biodegradable medical bandage.
[0034] Preparation of the modified chitosan microspheres: By weight, 10 parts of maleic anhydride were added to 400 parts of dimethyl sulfoxide and stirred to dissolve. Then, 8 parts of chitosan powder were added and dispersed evenly. The mixture was modified at 60°C for 8 hours, washed with acetone, and vacuum dried to obtain modified chitosan. 2 parts of modified chitosan were added to 200 parts of 1% acetic acid solution and stirred to dissolve. Then, 800 parts of liquid paraffin and 20 parts of emulsifier Span 60 were added. The mixture was first emulsified at 40°C and 900 r / min for 40 minutes. Then, 90 parts of 10% glutaraldehyde solution were added dropwise, and the pH was adjusted to 8 for crosslinking treatment for 4 hours. The precipitate was collected by centrifugation, washed successively with petroleum ether and isopropanol, and vacuum dried to obtain modified chitosan microspheres. Example 3
[0035] This embodiment provides a method for preparing a biodegradable medical bandage, including the following steps: S1. By weight, 95 parts of polylactic acid raw material, 2.2 parts of maleic anhydride and 0.3 parts of triethylamine were mixed and added to a torque rheometer. The mixture was melt-blended at 165°C and 35 r / min for 55 min to obtain product A. At 45°C, 95 parts of product A were added to 290 parts of xylene and stirred at 350 r / min to dissolve. After heating to 75°C, 2.6 parts of glycidyl methacrylate and 0.7 parts of triethylamine were added for grafting treatment for 45 min. After the reaction was completed, 190 parts of acetone were added to precipitate the product. The precipitate was filtered and dried under vacuum to obtain acrylate-grafted polylactic acid.
[0036] S2. By weight, 9 parts of acrylate-grafted polylactic acid were added to 95 parts of organic solvent dichloromethane and stirred to dissolve to obtain an oil phase. 3 parts of methacrylate-modified gelatin and 0.3 parts of photoinitiator LAP were added to 25 parts of deionized water and stirred to dissolve to obtain an aqueous phase at 45°C. 95 parts of the oil phase, 25 parts of the aqueous phase, and 1.4 parts of Span 80 were mixed and homogenized and emulsified at 5400 r / min for 9 min to obtain a spinning emulsion.
[0037] S3. The modified chitosan microspheres and the spinning emulsion are sprayed and electrospun. The voltage of the electrospinning emulsion is 14kV and the airflow velocity is 45m / s. The spraying velocity of the modified chitosan microspheres is 0.15mL / min. Photocrosslinking is performed (wavelength is 365nm, light intensity is 20mW / cm², and time is 25s) to obtain a biodegradable medical bandage.
[0038] Preparation of the modified chitosan microspheres: By weight, 11 parts of maleic anhydride were added to 450 parts of dimethyl sulfoxide and stirred to dissolve. Then, 9 parts of chitosan powder were added and dispersed evenly. The mixture was modified at 65°C for 7 hours, washed with acetone, and vacuum dried to obtain modified chitosan. 3 parts of modified chitosan were added to 250 parts of 1% acetic acid solution and stirred to dissolve. Then, 850 parts of liquid paraffin and 25 parts of emulsifier Span 80 were added. The mixture was first emulsified at 45°C and 950 r / min for 35 minutes. Then, 95 parts of 10% glutaraldehyde solution were added dropwise to adjust the pH to 8.4 and crosslinking was performed for 3 hours. The precipitate was collected by centrifugation, washed successively with petroleum ether and isopropanol, and vacuum dried to obtain modified chitosan microspheres.
[0039] Comparative Example 1 The difference between this comparative example and Example 1 is that polylactic acid (model L622E) was used instead of acrylate-grafted polylactic acid.
[0040] Comparative Example 2 The difference between this comparative example and Example 1 is that ordinary gelatin (item number G108394) is used instead of methacrylate-modified gelatin.
[0041] Comparative Example 3 The difference between this comparative example and Example 1 is that chitosan powder (product number C434547) was used instead of modified chitosan in the preparation of microspheres.
[0042] The medical bandages provided in the above embodiments and comparative examples were used to prepare samples with a thickness of 0.2 mm and a size of 2 cm × 3 cm. The performance of the samples was tested using the following methods: (1) Degradation rate test: The medical bandage samples of the present invention and comparative examples were weighed and the original mass (m1) was recorded. They were then buried in the soil for 60 days. After being taken out, the remaining mass (m2) after 60 days of degradation was recorded. The degradation rate formula is: D=(m1-m2) / m1×100%.
[0043] (2) Bursting performance test: The test shall be conducted in accordance with the requirements of GB / T 24218.5-2016 Textiles - Nonwovens - Part 5: Determination of mechanical penetration resistance (steel ball bursting method).
[0044] (3) Antibacterial rate test: The test shall be conducted in accordance with the requirements of GB / T 20944.3-2008 Evaluation of antibacterial properties of textiles Part 3: Vibration method.
[0045] The performance test data above are shown in Table 1.
[0046] Table 1 Performance Test Results
[0047] As can be seen from the above, the present invention first mixes polylactic acid raw material and maleic anhydride and then melt-blends them to obtain product A. Then, glycidyl methacrylate is used to graft product A to obtain acrylate-grafted polylactic acid. The acrylate-grafted polylactic acid is then added to an organic solvent and stirred to dissolve to obtain an oil phase. Methacrylate-modified gelatin and a photoinitiator are added to water and stirred to dissolve to obtain an aqueous phase. The oil phase, aqueous phase and Span 80 are mixed and emulsified to obtain a spinning emulsion. Finally, modified chitosan microspheres and the spinning emulsion are sprayed-electroblown and photocrosslinked to obtain a biodegradable medical bandage (Examples 1 to 3), which has better overall performance.
[0048] Compared to Example 1, using polylactic acid (model L622E) instead of acrylate-grafted polylactic acid resulted in a decrease in burst strength and a deterioration in antibacterial properties due to the lack of the effect of acrylate-grafted polylactic acid (Comparative Example 1); compared to Example 1, using ordinary gelatin (product number G108394) instead of methacrylate-modified gelatin resulted in a decrease in burst strength and a deterioration in antibacterial properties due to the lack of the effect of methacrylate-modified gelatin (Comparative Example 2); compared to Example 1, using chitosan powder (product number C434547) instead of modified chitosan for microsphere preparation resulted in a decrease in burst strength and a deterioration in antibacterial properties due to the lack of the effect of modified chitosan (Comparative Example 3).
Claims
1. A method for preparing a biodegradable medical bandage, characterized in that, Includes the following steps: S1. First, polylactic acid raw material and maleic anhydride are mixed and melt-blended to obtain product A. Then, glycidyl methacrylate is used to graft product A to obtain acrylate-grafted polylactic acid. S2. The acrylate-grafted polylactic acid is added to an organic solvent and stirred to dissolve to obtain an oil phase. The methacrylate-modified gelatin and photoinitiator LAP are added to water and stirred to dissolve to obtain an aqueous phase. The oil phase, aqueous phase and Span 80 are mixed and emulsified to obtain a spinning emulsion. S3. The modified chitosan microspheres and the spinning emulsion are sprayed, electrospun, and photocrosslinked to obtain a biodegradable medical bandage. The preparation steps of product A in step S1 are as follows: by weight, 90-100 parts of polylactic acid raw material, 1.8-2.4 parts of maleic anhydride and 0.2-0.4 parts of triethylamine are mixed and added to a torque rheometer, and melt-blended at 30-40 r / min at 160-170℃ for 50-60 min to obtain product A; The grafting treatment step S1 is as follows: by weight, 90-100 parts of product A are added to 280-300 parts of xylene at 40-50°C and stirred at 340-360 r / min to dissolve. After heating to 70-80°C, 2.4-2.8 parts of glycidyl methacrylate and 0.6-0.8 parts of triethylamine are added for grafting treatment for 40-50 min. After the reaction is completed, 180-200 parts of acetone are added to precipitate the precipitate. The precipitate is filtered and vacuum dried to obtain acrylate-grafted polylactic acid. The modified chitosan microspheres are prepared by: modifying chitosan powder with maleic anhydride to obtain modified chitosan; mixing the modified chitosan, liquid paraffin and emulsifier and then performing emulsification and crosslinking to obtain modified chitosan microspheres. The modification process is as follows: by weight, 10-12 parts of maleic anhydride are added to 400-500 parts of dimethyl sulfoxide and stirred to dissolve. Then, 8-10 parts of chitosan powder are added and dispersed evenly. The modification process is carried out at 60-70°C for 6-8 hours. The mixture is washed with acetone and dried under vacuum to obtain modified chitosan. The emulsification and crosslinking steps are as follows: by weight, 2-4 parts of modified chitosan are added to 200-300 parts of 1% acetic acid solution and stirred to dissolve. Then, 800-900 parts of liquid paraffin and 20-30 parts of emulsifier are added. The mixture is first stirred and emulsified at 900-1000 r / min under 40-50℃ conditions for 30-40 min. Then, 90-100 parts of 10% glutaraldehyde solution are added dropwise to adjust the pH to 8-9 and crosslinking is performed for 2-4 h. The precipitate is collected by centrifugation, washed successively with petroleum ether and isopropanol, and vacuum dried to obtain modified chitosan microspheres.
2. The method for preparing a biodegradable medical bandage according to claim 1, characterized in that, The preparation steps of the spinning emulsion in step S2 are as follows: by weight, 8-10 parts of acrylate-grafted polylactic acid are added to 90-100 parts of organic solvent and stirred to dissolve to obtain an oil phase; 2-4 parts of methacrylate-modified gelatin and 0.2-0.4 parts of photoinitiator LAP are added to 20-30 parts of deionized water and stirred to dissolve at 40-50°C to obtain an aqueous phase; 90-100 parts of the oil phase, 20-30 parts of the aqueous phase and 1-2 parts of Span 80 are mixed and homogenized and emulsified at a speed of 5000-6000 r / min for 8-10 min to obtain the spinning emulsion.
3. The method for preparing a biodegradable medical bandage according to claim 1, characterized in that, The conditions for spraying-electroblotting in step S3 are as follows: the voltage for electroblotting the spinning emulsion is 12~16kV, and the airflow velocity is 40~50m / s; the spraying velocity of the modified chitosan microspheres is 0.1~0.2mL / min.
4. The method for preparing a biodegradable medical bandage according to claim 1, characterized in that, The emulsifier is selected from one or more of Span 20, Span 60 or Span 80.
5. A biodegradable medical bandage, characterized in that, It is prepared according to any one of claims 1 to 4.
Citation Information
Patent Citations
A biodegradable medical polymer bandage and its preparation method
CN117618624B
Method of making graft copolymers from sodium poly (aspartate) and the resulting graft copolymer
CN102216336A
Preparation method of polylactic acid / polycaprolactone antibacterial blend fiber
CN117328162A